Preparation of phosphorus-containing epoxy emulsion and flame retardancy of its thermoset. (August 2014) - Qin, Yongsheng; Xu, Guilong; Wang, Yi; Hu, Jian
In this study, the effects of the opening ratio and neutralization degree of diethanolamine to the formation of epoxy emulsion were examined. o -Cresol formaldehyde epoxy resin was modified with 9, 10-dihydro-9-xa-10-phosphaphenanthrene-10-oxide and diethanolamine and was then neutralized by acetic acid to obtain a phosphorus-containing epoxy emulsion by the phase inversion method. The microstructure and size distribution of the epoxy latex were characterized using transmission electron microscopy and the Malvern particle sizer, respectively. The glass transition temperatures of epoxy resins and their thermosets were characterized using differential scanning calorimetry. The flame retardancy of the phosphorus-containing epoxy thermosets was tested by the UL-94 test method, limiting oxygen index (LOI), and thermogravimetric analysis (TGA). The result shows that when the diethanolamine opening ratio was 22.5% and neutralization degree was 100.0%, a stable epoxy emulsion was obtained. When the phosphorus content of the epoxy resin was 2.5 wt%, the LOI value of the epoxy thermoset can reach 36.8 and pass the V-0 rating of the UL-94 test. TGA and scanning electron microscopy images of char residue of epoxy thermosets show that the flame-retardant mechanism of the phosphorus-containing epoxy thermoset was mainly attributed to a condensed-phase mechanism.